Effects of Ultrafine Fly Ash on Setting, Strength, and Porosity of Geopolymers Cured at Room Temperature - Deb, Partha Sarathi; Sarker, Prabir (American Society of Civil Engineers (ASCE), 2017)
This paper presents the effects of ultrafine fly ash on setting, strength and porosity of geopolymer paste specimens cured at 20°C. Addition of ultrafine fly ash reduced setting time and improved compressive strength of geopolymers based on fly ash only or fly ash blended with 15% ground granulated blast-furnace slag (GGBFS) or 10% ordinary portland cement (OPC). With the addition of ultrafine fly ash, a reduction in porosity was observed by the mercury intrusion porosimetry (MIP) and a denser microstructure was observed by the scanning electron microscope (SEM) photographs. Thus, for room temperature curing conditions, a control on the setting time and improvements of strength and porosity of geopolymers could be achieved by varying the percentage of ultrafine fly ash.